Model Training for Involving Children in Housework as Development of Children's Strong and Independent Characters in the Family Environment - Hardika, Hardika; Iriyanto, Tomas; Soraya, Dila Umnia; Aisyah, Eny Nur (Faculty of Education Universitas Negeri Malang, 2023)
The involvement of children in household work is actually able to train the character formation of children's resilience and independence. However, today's parents have an orientation to educate and take care of children which is more directed towards the success of children in completing school academic tasks rather than completing daily household chores at home. As a result, many children experience independence disorders in completing their daily homework. This training aims to increase the knowledge and ability of parents about models and strategies for managing children's involvement in completing household tasks at home. The solution offered in this activity is training related to the model of involving children in household work at home for 76 parents and educators at the Tunas Bangsa Bakalan Krajan PAUD POS, Sukun District, Malang City. This training is conducted one day offline and 30 days online mentoring. The training was conducted using interactive discussion methods, training and focus group discussions. Material delivery includes (1) positive parenting for children's development and activities, (2) parental skills and attitudes that support the development of children's potential and personality at home, and (3) problems of parental involvement in the process of educating children's resilience and independence through involving children in solving problems. House chores. The steps of this training activity include identification of partner institutions' problems, identification of partner institutions' learning needs, preparation of training material frameworks, determination of training sources, preparation of training tools, training implementation, monitoring and evaluation, and follow-up activities plans. This training increases the knowledge and ability of parents and educators in implementing the model of involving children in household work and having awareness of the important impact of involving children in household work for the formation of independence and resilience in children's lives.